"Getting the Right People on the Bus": Recruitment, selection and integration for the branded organization. Issue 2 (April 2016) - Russell, Stephanie; Brannan, Matthew J.
Abstract: This paper examines how employer branding is used and embedded through the organizational HR practices; specifically recruitment, selection and integration. The paper adds to the growing literature on employer branding by specifically focussing upon concrete HR practices, which are often left unexplored in contemporary accounts of branding practices. Our research question is to explore the specific role that these practices play in the enactment of employer branding and assess their implications. Moreover, in order to better understand the wider significance of employer branding, scholarship needs to explore these processes in contexts where brand recognition is less prevalent. Drawing on a large multi-national organization (CollinaTrade) involved in the provision of products and services in the construction industry, the organization's minimalist focus on consumer brands makes them a useful case study for evaluating the work of employer branding outside consumer facing industries. This paper points to the significance of viewing employer branding as a management tool in terms of cultural reinforcement and symbolic representations at work and the way in which this work through HR practices. Our data shows that the logic of employer branding in contexts where the brand is less significant, is essentially contradictory, requiring both individualism and uniformity which may have a greater impact on workplace identities than previously thought.